Influence of transition metal doping on the tribological properties of pulsed laser deposited DLC films. Issue 1 (January 2015) - Gayathri, S.; Kumar, N.; Krishnan, R.; Ravindran, T.R.; Amirthapandian, S.; Dash, S.; Tyagi, A.K.; Sridharan, M.
Abstract: Doped or alloyed diamond-like carbon (DLC) films exhibit superior properties compared to undoped DLC films. But the choice of dopant plays a vital role in tailoring specific properties of the DLC film desired for specific application. In the present work, a comparative study has been carried out in order to bring out the effect of transition metal (TM) doped DLC film on the tribological properties. Nanocomposite DLC/TM (TM=Ag, Ti and Ni) films were deposited by nanosecond pulsed laser deposition (PLD) technique on to AISISS304 substrates. Films microstructure and chemical behavior was studied by glancing incidence X-ray diffraction (GI-XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and high resolution transmission electron microscopy (HRTEM). The sp 2 and sp 3 fraction in the films are well described by electron energy loss spectroscopy (EELS) analysis. The Raman spectra of DLC/TM films showed peak shift towards lower wavenumber indicating the reduction of internal compressive stress. Formation of TM nanoclusters and TiC phases were confirmed in DLC/TM films by GI-XRD, XPS and HRTEM. DLC film doped with nanocrystalline Ag showed low friction behavior due to the formation of large amount of sp 2 lubricant phase. However, high friction coefficient measured in DLC film doped with Ni and Ti. Such a high friction is explained by the presence of hard TiC and sp 3 phase in the DLC/Ti and DLC/Ni films respectively.